Acupressure Complementary Therapy Training and Assistance for Excellent Midwife in Entrepreneurial Development for Alumni - Cut Yuniwati; Noviyanti; Ratna Dewi; Yeni Rimadeni (Institute of Computer Science (IOCS), 2022)
The success of maternal health efforts and the health status of a community can be seen from the number of Maternal Mortality Rates (MMR). Midwives are one of the health workers who have an important position in reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Midwives provide continuous and comprehensive midwifery services, focusing on aspects of prevention, promotion based on partnerships and community empowerment together. Complementary traditional health services are the application of traditional health that utilizes biomedical and biocultural sciences. Activity Purpose To increase the knowledge/understanding and skills of midwifery majors alumni of the Poltekkes Kemenkes Aceh on Complementary Acupressure Therapy For Excellent Midwife in Entrepreneurial Development for Alumni. The dedication method used in this activity is education, training and assistance in increasing the knowledge and abilities of alumni about complementary acupressure therapy for excellent midwife. The results of the dedication show that the provision of education about complementary acupressure therapy increases the alumni's knowledge about complementary acupressure therapy. The average alumni knowledge during the pre-test, which was around 51.81% of the number of questions answered correctly by alumni, experienced a change for the better after the post-test to around 95.45%. This community service activity ran smoothly, starting from the training activities and continuing with alumni assistance activities in providing acupressure therapy. This activity has enormous benefits felt by the participants. Apart from increasing knowledge.